Anti-HMGCR myopathy: a first case report from North Africa and literature insights - Abida, Houssem; Zamali, Imen; Rachdi, Imène; Saied, Zakaria; Ben Hmid, Ahlem; Samoud, Samar; Galai, Yousr; Daoud, Fatma; Boussema, Fatma; Ben Sassi, Samia; Aydi, Zohra; Ben Ahmed, Mélika (Frontiers in Immunology, 2025)
Anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (anti-HMGCR) myopathy is a rare idiopathic inflammatory myopathy characterized by severe muscle damage and minimal extra-muscular involvement. This report presents the first documented case of severe, treatment-resistant HMGCR-myopathy in a Tunisian and North African patient. A 43-year-old man with no significant medical history experienced progressive muscle weakness over one year, leading to difficulty walking. Examination revealed pronounced proximal muscle weakness, particularly in the lower limbs, with significant quadriceps atrophy. Laboratory results indicated elevated Creatine Kinase (CK) levels at 10000 UI/l and Lactate dehydrogenase (LDH) at 400 UI/l. Electromyography confirmed myogenic damage, and muscle biopsy revealed extensive muscle necrosis and regeneration with moderate inflammatory infiltrates. Screening for anti-HMGCR antibodies was positive. Initial treatment with high-dose prednisone showed a good response but led to flares upon tapering. Subsequent treatment with methotrexate, azathioprine, and rituximab resulted in partial clinical and biological improvement. This case underscores the challenges in diagnosing and managing anti-HMGCR myopathy due to limited awareness and access to testing.